Monomer Controlled Switchable Copolymerization: A Feasible Route for the Functionalization of Poly(lactide). Issue 17 (17th March 2021) - Huang, Yuezhou; Hu, Chenyang; Zhou, Yanchuan; Duan, Ranlong; Sun, Zhiqiang; Wan, Pengqi; Xiao, Chunsheng; Pang, Xuan; Chen, Xuesi
Abstract: Switchable polymerization is an attractive strategy to enable the sequential selectivity of multi‐block polyesters. Besides, these well‐defined multi‐block polyesters could enable further modification for wider applications. Herein, based on the reversible insertion of CO2 by Salen‐Mn III, a new monomer controlled self‐switchable polymerization route was developed. Chemoselective ring opening copolymerization of O ‐carboxyanhydrides (OCAs) and lactide (LA) was explored without cocatalyst. The sequential conversion of OCAs and LA into the polymer chain could form multi‐block polyesters. Based on this strategy, a series of multi‐block polyesters with different pendant groups were synthesized. Furthermore, by modifying the propargyl‐containing copolymers with quaternary ammonium groups, we have realized antibacterial functionalization of PLA. These results imply the potential application of this strategy for the fabrication of functional polymers for biomedical applications. Abstract : A new monomer controlled self‐switchable copolymerization was developed with Salen‐Mn III ‐Cl complexes. Chemoselective copolymerization of O ‐carboxyanhydrides (OCAs) and lactide (LA) was explored without cocatalyst or chain transfer agent (CTA).